Infectious Tolerance as Seen With 2020 Vision: The Role of IL-35 and Extracellular Vesicles - Sullivan, Jeremy A.; AlAdra, David P.; Olson, Brian M.; McNeel, Douglas G.; Burlingham, William J. (Frontiers in Immunology, 2020)
The concept of “Infectious Tolerance”, originally proposed in the early 1970s by Gershon and Kondo [1] and expanded upon by Herman Waldman[2], pre-dates the discovery of specialized T regulatory cells and Foxp3 by several years. Although the specialized CD4 T regulatory cells of the immune system that were responsible for initiation of peripheral tolerance came into view with the later work of Sakaguchi [3], Rudensky [4], and others, what caused the “infectious” nature of tolerance enforced by Tregs was not immediately clear. That is to say, the transferable nature of immunoregulation that Qin et al [2] had shown so clearly in 1993, whereby one set of (induced) regulatory T cells could convert newly-arising T cells such that they would also become tolerant, lacked any mechanism. The problem was that the type of immunoregulatory cytokines known at the start of the 21st century, TGFbeta and IL10, were known as powerful primary immunosuppressives, but neither were known for their ability to induce regulatory activity in other, non-Treg cell types. Here we consider a novel form for the cytokine IL-35, ideally suited to the task of propagating tolerance by “infecting” other lymphocytes.